Niches within a niche: ecological differentiation of subterranean amphipods across Europe's interstitial waters. Issue 6 (8th February 2019) - Fišer, Cene; Delić, Teo; Luštrik, Roman; Zagmajster, Maja; Altermatt, Florian
Abstract : Species that successfully colonized subterranean environments are subject to two opposing selection processes. Stringent abiotic factors select for convergent adaptations, such as loss of eyes and pigments, while interspecific competition drives between‐species divergence. Subterranean species can resolve opposing selection by adaptation to physically different microhabitats. Yet, species frequently co‐occur in physically homogeneous subterranean habitats, like interstitial. These co‐occurrences in such a narrow ecological context can be explained either by equalizing mechanisms, in which neither of the co‐occurring species has a competitive advantage, or by more complex niche models that include species' differentiation along a trophic niche axis. We tested these hypotheses using the amphipod genus Niphargus . We analysed Europe‐wide co‐occurrence records of Niphargus species from interstitial habitats, split into six independent large‐scale regions. Firstly, we addressed whether species' pairwise co‐occurrences are random using a probabilistic model. Secondly, we tested whether species cluster into distinct functional–morphological groups and whether ecologically or phylogenetically distinct species are more likely to co‐occur. We found that 68% of species co‐occurrences were not different from random expectation, indicating that most species had access to most sites within each region. The remaining 32% co‐occurred either significantly more or less often than expected by chance. Cluster analysis of functional morphological characters showed that interstitial species belong to two feeding types, micro‐ and macrofeeders, likely representing two peaks of the interstitial adaptive landscape, and hinting that niche divergence, as a mechanism allowing coexistence, is favoured. Finally, we found that the number of co‐occurrences increases with increasing differentiation of functional morphology, but not phylogenetic differences. We conclude that ecological differentiation may be important in shaping such interstitial communities.